Insecticidal activity of selected weeds extract for controlling rice weevil, Sitophilus oryzae / Nurul Hana Ismail - Ismail, Nurul Hana (2024)
Rice, Oryza sativa (Linn.), is a valuable grain that has become a staple food for a large part of the global population. It is widely consumed in Malaysia and is persistently infected with a variety of insect pests during the storage period. The rice weevil, Sitophilus oryzae, is the major pest of stored product insects. For the control of insects, synthetic pesticides have been used, which have detrimental effects on the environment and health. Therefore, botanical pesticides from weeds are currently being suggested as an alternative to synthetic insecticides. The present study was conducted to evaluate the insecticidal activities of selected weed extracts against S. oryzae, using M. malabatrichum, C. hirta, C. odorata, and A. conyzoides extracts. Different application techniques were used to determine the effective active extracts for controlling S. oryzae, and the phytochemical compounds of the insecticidal activity in the extracts needed to be determined. Crude extracts were extracted using the maceration technique. Mortality tests of contact toxicity, fumigation tests with and without rice grain, and antifeedant tests were conducted using Petri dishes, fumigation chambers, and plastic containers, respectively. A repellency test was conducted using an area preference bioassay. To find plant compounds that can kill insects, phytochemical screening, total phenolic content, total flavonoid content, GCMS, and HPLC were all used. The highest mortality for the contact toxicity test were from M. malabatrichum, C. hirta (ethanol extract), and C. odorata, A. conyzoides (acetone extract), with 100% mortality. The fumigant toxicity tests were for C. hirta and C. odorata ethanol and acetone extracts, respectively, with 100% mortality. The highest mortality for the fumigant toxicity test without rice grain was from all the samples with 100% mortality except C. odorata acetone extract. M. malabatrichum ethanol extract had the highest antifeedant test mortality (100% mortality). The highest mortality (100%) for the repellent test was from ethanol extract (C. odorata, A. conyzoides) and acetone extract (C. hirta, C. odorata, and A. conyzoides). Ethanol extracts had a higher mortality percentage compared to acetone extracts. The mortality of S. oryzae was higher when using the method of fumigation without rice grain. C. odorata has good potential to be used as a botanical pesticide, with a high mortality percentage and a high repellency percentage against S. oryzae. It is recommended for further analysis using liquid chromatography-mass spectrometry (LCMS) to analysed active compounds of insecticidal activity, conduct field tests, and formulate C. odorata leaves as biopesticides in the future.